The Role of Tax Systems in Reducing Income Inequality: A Literature Review - Tjan, Julianty Sidik (Advances in Taxation Research, 2024)
Purpose: This study aims to examine the effectiveness of the progressive taxation system in reducing income inequality and its role in addressing the issue. Research Design and Methodology: Using a qualitative research approach, this study conducted a comprehensive review of the existing literature, including theoretical frameworks and empirical studies, to synthesize critical insights on the impact of progressive taxation on income distribution. Findings and Discussion: The findings suggest that progressive taxation, characterized by higher tax rates for individuals with higher incomes, can significantly reduce income inequality. Empirical evidence from various studies supports the idea that countries with more progressive tax systems tend to have lower levels of income inequality. However, the effectiveness of progressive taxation depends on factors such as the overall design of the tax system, enforcement mechanisms, and broader economic conditions. Implications: The results of this study emphasize the importance of prioritizing fair tax policies and strengthening enforcement measures to promote social justice and inclusive economic growth. Future research should explore innovative tax policy solutions to face new challenges such as digitalization, globalization, and environmental sustainability.